2017
DOI: 10.18535/jmscr/v5i1.109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile, Aetiology, and Short Term Outcome of Convulsive Status Epilepticus in Children in Eastern India

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Similar risk factors were found in other studies. 5,7,11,16 Age, prior neurological status, lag time for receiving first AED and response to it did not have significant effect on mortality in present study. Gulati et al and Kumar et al reported high mortality in children less than 3 years with CSE.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Similar risk factors were found in other studies. 5,7,11,16 Age, prior neurological status, lag time for receiving first AED and response to it did not have significant effect on mortality in present study. Gulati et al and Kumar et al reported high mortality in children less than 3 years with CSE.…”
Section: Discussioncontrasting
confidence: 50%
“…Mortality rate in children with CSE ranged from 14-33% in Indian studies while studies from developed countries report mortality of 9-11%. 5,7,8,16,18 The risk factors for mortality that were significant in this study included longer duration of status, acute symptomatic etiology, requirement of ventilatory support and circulatory impairment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Das et al also observed that fever was most common symptom associated with SE and mostly seen in younger age group of children <5 years 8. This may be because acute infections are important cause of SE in all age groups.…”
mentioning
confidence: 92%
“…In our study mortality of SE was 8.7%. Das et al observed mortality of 15% (n=6/40) 8. Madhu et al observed mortality of 26.4% (n=23/87) and Kumar et al observed mortality of 31.4% (n=22/70).…”
mentioning
confidence: 99%